Inflammatory cell types in Reinke’s edema - Bengü Çobanoğlu, H.; Arslan, Selçuk; Çobanoğlu, Ümit; İmamoğlu, Mehmet (ENT Updates, 2017)
Objective: To evaluate the histopathological findings in Reinke’s edema and correlate them with otorhinolaryngologic symptoms other than dysphonia. Methods: Patients diagnosed with Reinke’s edema as the source of dysphonia from January to December 2016 were included in this retrospective study. The histopathological findings in Reinke’s edema and the correlation with otorhinolaryngologic symptoms other than dysphonia were evaluated. Results: A total of 13 patients (3 females, 10 males) with Reinke’s edema all of whom were smokers underwent surgery. In all of the specimens, the main histopathological finding was edema in the lamina propria of the vocal folds. The dominant inflammatory cell type in the stroma was determined by evaluating the whole microscopic subepithelial zone. The cell types included plasma cells, lymphocytes, monocytes, and neutrophils. Conclusion: In Reinke’s edema the main pathologic finding is the collection of edematous fluid in Reinke’s space. As our study was limited by the small number of cases, we could not find any statistically significant correlation between the inflammatory cell types and clinical characteristics of Reinke’s edema.